Changes in Carbon Cycling during Development of Successional Agroforestry - Selecky, Tomas; Bellingrath-Kimura, Sonoko D.; Kobata, Yuji; Yamada, Masaaki; Guerrini, Irae A. [UNESP]; Umemura, Helio M.; Dos Santos, Dinaldo A. (Mdpi Ag, 2017)
Successional agroforestry systems (SAFS) mimic the structure of natural forests while providing economical outputs. This study clarifies how carbon cycling and carbon sequestration change during successional development of SAFS. In Brazil, three successional stages of SAFS, 6, 12, and 34 years old, were compared in terms of carbon balance. Aboveground biomass, fruit harvest, litterfall, soil respiration, and soil organic carbon were measured for two years and analyzed. Carbon sequestration expressed by net primary productivity increased with age of SAFS from 9.8 MgCha(-1)year(-1) in 6-year-old system to 13.5 MgCha(-1)year(-1) in 34-year-old system. Accumulation of plant biomass and increased internal carbon cycling in SAFS led to an intensive sequestration of carbon. SAFS can be a sustainable way of agricultural production on vulnerable tropical soils.
Keywords: successional agroforestry; carbon cycling; soil fertility; Brazil; aboveground biomass; SOC; litterfall; respiration